2021
DOI: 10.3390/polym13142358
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Stone Matrix Asphalt Modified with Polyvinyl Chloride and Nano Silica

Abstract: In this study, the effects of polyvinyl chloride (PVC) and nano silica (NS) as modifiers on the properties of stone matrix asphalt (SMA) were studied. The experiment was performed with five modes: 1% NS was mixed into SMA; 5% PVC was mixed into SMA; and the ratio of NS was changed (1, 2, and 3%) with 5% PVC being mixed into SMA. The properties of modified and unmodified SMA materials were determined and compared by performing the penetration test, softening points test, viscosity measurements, dynamic shear rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The results revealed that TSR of the unmodified HMA specimen was about 79%, while that of 4.5% SBS + 6% NS was about 97%. NS has a very small particle size with a large exposed area; that is why it replaces a large quantity of bitumen and improves the modified bitumen structure [27]. TSR was increased as the percentage of NS was increased up to 4.5% SBS + 6% NS, and then was decreased.…”
Section: Results Of Its Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that TSR of the unmodified HMA specimen was about 79%, while that of 4.5% SBS + 6% NS was about 97%. NS has a very small particle size with a large exposed area; that is why it replaces a large quantity of bitumen and improves the modified bitumen structure [27]. TSR was increased as the percentage of NS was increased up to 4.5% SBS + 6% NS, and then was decreased.…”
Section: Results Of Its Testmentioning
confidence: 99%
“…To examine the responsiveness of the dependent variables (MR) to the modifier and temperature, an experimental design, factorial design was utilized [26][27][28]. A mixture of several factors was used in the experimental design to check the effectiveness of such variables on the response variable.…”
Section: Experimental Design Of Mrmentioning
confidence: 99%